Left Ventricular Amyloid Deposition in Patients with Heart Failure and Preserved Ejection Fraction - Mohammed, Selma F. (2014)
OBJECTIVE: Determine the frequency of left ventricular (LV) amyloid in heart failure with preserved ejection fraction (HFpEF). BACKGROUND: LV amyloid deposition can cause diastolic dysfunction and HFpEF. METHODS: Autopsy LV specimens from patients with ante-mortem diagnosis of HFpEF without clinically apparent amyloid (n=109) and Control subjects (n=131) were screened with sulfated alcian blue and subsequent Congo red staining with micro-dissection for mass spectrometry-based proteomics to determine amyloid type. Fibrosis was assessed with quantitative whole-field digital microscopy. RESULTS: Presence of wtTTR amyloid was associated with age at death and male sex; but the age-and sex-adjusted prevalence of wtTTR amyloid was higher in HFpEF than Control (Odds ratio 3.8, 95% confidence interval 1.5–11.3; p=0.03). Among HFpEF patients, moderate or severe interstitial wtTTR deposition, consistent with senile systemic amyloidosis as the primary etiology of HFpEF, was present in five (5%) patients (80% male), with mild interstitial and/or variable severity of intramural coronary vascular deposition in 13 (12%). While wtTTR deposition was often mild, adjusting for age and presence of HFpEF, wtTTR amyloid was associated with more fibrosis (p=0.005) and lower age, sex, and body size-adjusted heart weight (p=0.04). CONCLUSION: Given the age- and sex-independent association of HFpEF and wtTTR deposition and an emerging understanding of the pathophysiology of the amyloidoses, the current findings support further investigation of the role of wtTTR in the pathophysiology of HFpEF.